1972
DOI: 10.1084/jem.136.6.1356
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Dependent Histamine Release From Rabbit Platelets

Abstract: We have studied the leukocyte-dependent mechanism of histamine release (LDHR) from rabbit platelets, a complement-independent mechanism which has been implicated in the deposition of immune complexes in acute serum sickness of rabbits. It was found by chromatography and passive transfer of serum from immunized rabbits that the antibody responsible for the LDHR was of IgE type. By electron microscope study of the reaction, the leukocyte involved in agglutination of platelets and release of their histamine conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
245
0
21

Year Published

1975
1975
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,174 publications
(267 citation statements)
references
References 24 publications
1
245
0
21
Order By: Relevance
“…Moreover, 5-HT released from aggregated platelets may cause bronchoconstriction manifested as wheezing in a patient with pulmonary embolism (109). It has been shown that 5-HT may be a potent mediator in the acute tracheal contraction elicited by platelet-activating factor (PAF) in dogs (85); PAF is a lipid mediator secreted during immune degranulation (7).…”
Section: Sources Of 5-ht Within the Pulmonary Systemmentioning
confidence: 99%
“…Moreover, 5-HT released from aggregated platelets may cause bronchoconstriction manifested as wheezing in a patient with pulmonary embolism (109). It has been shown that 5-HT may be a potent mediator in the acute tracheal contraction elicited by platelet-activating factor (PAF) in dogs (85); PAF is a lipid mediator secreted during immune degranulation (7).…”
Section: Sources Of 5-ht Within the Pulmonary Systemmentioning
confidence: 99%
“…Originally described as platelet activating factor (PAF), a soluble intermediate released following exposure of sensitized rabbit basophils to specific antigens (Benveniste, Henson & Cochrane, 1972), this active material is now known to be a series of phospholipids, 1-0-alkyl-2-acetyl-sn-glyceryl-3-phosphorylcholine, and is referred to as AGEPC (Demopoulos, Pinckard & Hanahan, 1979,) or Pafacether (Benveniste, Tence, Varrene, Bidault, Boullet & Polonsky, 1979). Like many other materials released in allergic reactions, Paf-acether elicits inflammatory responses, as has been demonstrated in the skin (Stimler, Bloor, Hugli, Wykle, McCall & O'Flaherty, 1981;Wedmore & Williams, 1981a;Humphrey, McManus, Satouchi, Hanahan & Pinckard, 1982;Paul & Page, 1982) and paw (Bonnet, Loisseau, Orvoen & Bessin, 1981;Vargaftig & Ferreira, 1981;) of experimental animals and in the skin of man (Pinckard, Kniker, Lee, Hanahan & McManus, 1981;Basran, Page, Paul & Morley, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…PAF was initially recognized as a product of IgE-sensitized rabbit basophils (2) and was identified with 1-0-alkyl-2-sn-glyceryl-3-phosphorylcholine (3)(4)(5). It was subsequently shown that PAF is synthesized after appropriate stimulation by monocytes/macrophages (6)(7)(8)(9), polymorphonuclear neutrophils (7,10,11), platelets (12) and endothelial cells (13)(14)(15) .…”
mentioning
confidence: 99%
“…It was subsequently shown that PAF is synthesized after appropriate stimulation by monocytes/macrophages (6)(7)(8)(9), polymorphonuclear neutrophils (7,10,11), platelets (12) and endothelial cells (13)(14)(15) . PAF induces aggregation and degranulation of platelets (2,16), stimulates contraction of smooth muscle (17), promotes chemotaxis and granule secretion of neutrophils (18)(19) and monocytes (20), increases vascular permeability, and alters the vascular tone (21).…”
mentioning
confidence: 99%